2015
DOI: 10.1161/circresaha.116.304564
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cells Contribute to Cardiomyocyte Regeneration After Injury

Abstract: Rationale:The contribution of bone marrow-borne hematopoietic cells to the ischemic myocardium has been documented. However, a pivotal study reported no evidence of myocardial regeneration from hematopoieticderived cells. The study did not take into account the possible effect of early injury-induced signaling as the test mice were parabiotically paired to partners immediately after surgery-induced myocardial injury when crosscirculation has not yet developed. Objective:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 38 publications
7
59
0
Order By: Relevance
“…Previous lineage studies concluded that most proliferation-labeled cardiomyocytes arise from preexisting cardiomyocytes 7,8 , which discounts the possibility that our observations can be explained by proliferation of a progenitor followed by cardiomyocyte differentiation. Fusion of cardiomyocytes with hematopoietic or other cell types can occur 2729 , but this results in binuclear rather than mononuclear cells. Although we cannot formally exclude the possibility of DNA replication by preexisting binuclear or tetraploid cardiomyocytes with two subsequent rounds of division into MNDCMs, our observations are consistent with a proliferative response by MNDCMs that divide to generate more MNDCMs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous lineage studies concluded that most proliferation-labeled cardiomyocytes arise from preexisting cardiomyocytes 7,8 , which discounts the possibility that our observations can be explained by proliferation of a progenitor followed by cardiomyocyte differentiation. Fusion of cardiomyocytes with hematopoietic or other cell types can occur 2729 , but this results in binuclear rather than mononuclear cells. Although we cannot formally exclude the possibility of DNA replication by preexisting binuclear or tetraploid cardiomyocytes with two subsequent rounds of division into MNDCMs, our observations are consistent with a proliferative response by MNDCMs that divide to generate more MNDCMs.…”
Section: Resultsmentioning
confidence: 99%
“…BMCs, the most common stem cell for cardiac therapy, apparently undergo engraftment through a combination of cell fusion and to a lesser degree by direct transdifferentiation events 25 . Membrane fusion is dependent upon signaling mechanisms involving paxillin induced focal adhesions and recycling of integrins as demonstrated between macrophages and myoblasts 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The second category includes adult, undifferentiated progenitor cells such as bone marrow mononuclear cells (BMCs) (147,260,318,396), MSCs (11,119,137), and resident adult cardiac progenitors (CPCs) (62,228). Although most of these cell types entered the clinical arena based on the hypothesis that they possessed myogenic differentiation capacity (191), further mechanistic studies revealed critical contributions of their anti-inflammatory and antifibrotic properties, as well as stimulation of endogenous cardiovascular progenitor and cardiomyocyte proliferation cell programs (144,219,229,291,349).…”
Section: Introductionmentioning
confidence: 99%
“…Although most of these cell types entered the clinical arena based on the hypothesis that they possessed myogenic differentiation capacity (191), further mechanistic studies revealed critical contributions of their anti-inflammatory and antifibrotic properties, as well as stimulation of endogenous cardiovascular progenitor and cardiomyocyte proliferation cell programs (144,219,229,291,349). Nonetheless, genetic lineage-fate mapping studies show that, under the proper conditions, endogenous CPCs (145,348,368), and to a smaller extent BMCs (289,396) and MSCs (60,144,290) produce new cardiomyocytes in the postnatal heart, albeit at a functionally insignificant level. Paradoxically, compared with ESC/iPSC-based strategies, engraftment of MSCs and CPCs is lower but leads to significant heart regeneration and recovery of heart function (62,97,119,137,143,144,147,174,175,228,229,284,290,321,322,385).…”
Section: Introductionmentioning
confidence: 99%